Clinical Features of COVID-19 in Elderly Patients - Giorgino, Riccardo; Migliorini, Filippo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint "Clinical Features of COVID-19 in Elderly Patients" is a crucial resource dedicated to the medical challenges posed by the pandemic, with a specific focus on its impact on elderly people. Given their vulnerability, understanding the clinical aspects of COVID-19 in this demographic is paramount. This reprint compiles a wide array of studies and current knowledge tailored to address the unique challenges faced by elderly people during the pandemic. It surpasses literature reviews, offering critical analysis and in-depth discussions. Its primary goal is to encourage critical analyses and discussions about the clinical characteristics of COVID-19 in elderly people. Targeted towards medical professionals, researchers, and healthcare practitioners, it aids in the development of tailored treatment approaches and care protocols. As the COVID-19 pandemic persists, this reprint remains essential for those dedicated to combating the virus, enhancing elderly patients' care, and promoting public health.